Psikoterapi Pembacaan Surah Yasin di Rumah Sakit Jiwa Aceh - Zulihafnani Zulihafnani; Mutiara Mawaddah (TAFSE: Journal of Qur'anic Studies, 2022)
Aceh's National Narcotics Agency announced that the number of drug addicts in Aceh Province reached 83 thousand people. Various efforts have been made to treat these patients, one of which is by psychotherapy of reading surah Yasin as carried out by the Aceh Mental Hospital. This study wants to examine the application and impact of psychotherapy by reading Surah Yasin as one of the methods of recovering from the effects felt by drug victim patients at the Aceh Mental Hospital after consuming illegal drugs. This research is a qualitative research by using a descriptive approach. Data were collected by observation, interview, and documentation techniques. The results showed that the application of the psychotherapy of the recitation of Surah Yasin to drug patients was carried out every Friday night after the completion of the Maghrib prayers congregation. This activity was carried out in congregations with the guidance of the addiction counselor. The therapy program for the reading of Surah Yasin was also accompanied by several other religious programs, such as tahsin and tausiyah implemented by the Ministry of Religious Affairs of Banda Aceh City. The impact felt by patients from psychotherapy is to bring out calm, tranquillity and comfort. In addition, psychotherapy also encourages the emergence of a sense of surrender of patients to God, feeling the aura of a good environment, reminding them of their late parents, a desire to pray, feeling more grateful, and remembering the purpose of life. Badan Narkotika Nasional provinsi Aceh mengumumkan angka pecandu atau penyalahgunaan narkoba di Aceh mencapai 83 ribu orang. Berbagai upaya telah dilakukan untuk menangani pasien tersebut, salah satunya dengan psikoterapi pembacaan Surah Yasin sebagaimana dilakukan Rumah Sakit Jiwa Aceh. Penelitian ini ingin mengkaji penerapan dan dampak dari psikoterapi pembacaan Surah Yasin sebagai salah satu metode pemulihan dari efek yang dirasakan pasien korban narkoba di Rumah Sakit Jiwa Aceh setelah mengkonsumsi obat-obatan terlarang. Penelitian ini berbentuk kualitatif dengan menggunakan pendekatan deskriptif. Data dikumpulkan dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan psikoterapi pembacaan Surah Yasin pada pasien narkoba dilaksanakan pada setiap malam Jumat setelah selesai melaksanakan salat Maghrib berjamaah. Pembacaan Surah Yasin dilakukan berjamaah dengan dibimbing oleh konselor adiksi. Program terapi ini juga dibarengi dengan program keagamaan lain, seperti tahsin dan tausiyah yang dilaksanakan oleh Kementerian Agama Kota Banda Aceh. Dampak yang dirasakan pasien dari psikoterapi tersebut ialah memunculkan ketenangan, ketentraman dan kenyamanan. Di samping itu, psikoterapi juga mendorong munculnya rasa berserah diri pasien kepada Allah, merasakan aura lingkungan yang baik, mengingatkan mereka kepada mendiang kedua orang tua, muncul keinginan untuk berdoa, merasa lebih bersyukur, dan ingat akan tujuan hidup.